Presenting a Model of Decentralization for Iran\'s Education - Ali Rostami Kia; Sadegh Maleki Avarsin; Jahangir Yari Haj Atalo (Iranian Journal of Educational Research)
Objective: The present study was undertaken with the objective of developing a theoretical framework predicated upon the determinants influencing the decentralization of education in Iran. Methods: In the course of this investigation, both internal and external determinants pertinent to the decentralization of educational systems were delineated. This study employed a qualitative methodological approach, specifically utilizing inductive content analysis. The qualitative segment of the study encompassed a statistical population comprised of experts specializing in educational management, as well as education administrators from the provinces of East Azerbaijan and West Azerbaijan. From this cohort, a selection of 20 knowledgeable experts with substantial experience in educational management was made through purposeful sampling. These individuals engaged in research interviews that were conducted in a semi-structured format. The dependability of the interviews was substantiated by soliciting evaluations from professionals in the domain of educational management. The data obtained from the interviews were meticulously analyzed and systematically coded. Results: The outcomes of the final conceptual framework revealed that the factors identified within the qualitative component encompassed both internal and external variables influencing the decentralization of education in Iran. Out of the 858 identified indicators, 28 primary components were discerned, and these dimensions and components were subsequently designated in accordance with the prevailing literature, context, and theoretical frameworks. Conclusions: By leveraging the insights garnered from these findings, a model was articulated, emphasizing the critical factors underlying the decentralization of education in Iran.